Modern music industry perspectives on music marketing using social media platforms - Brännkärr, Anna-Sofia (2023)
The music industry and the importance of marketing music through online media platforms and distribution services has been on public discussion for a while now. Succeeding in the music industry seems harder than ever, even though at the same time technologies have given us global, cost effective possibilities that did not exist before. This thesis aims to answer the question of whether or not social media usage for music marketing is an inevidable part of being an artist in the modern music industry and whether or not it is more important to be a good marketer than a great musician. These questions are looked at through a lens of the Finnish music industry and applies metal music views to these questions as an underground genre example.